Malaise in the Western Middle Classes - Louis Chauvel; Anne Hartung (Luxembourg Income Study (LIS), 2016)
The living conditions and well-being of the middle class are traditionally considered an expression of how society is progressing. Yet growing inequality and the polarization of incomes observed in Western countries due to globalization, the recession and rapid technological change, is leading to what has been described as a "malaise of the middle class". This article presents the evolution of the income distribution in selected Western countries and discusses the possible impact of the threat created by downward mobility and the erosion of the middle class in today's society.
Keywords: 330